The Regularized Operator Extrapolation Algorithm - Семенов, Володимир Вікторович; Харьков, О. С. (Київський національний університет імені Тараса Шевченка, 2023)
This work is devoted to the study of new algorithm for solving variational inequalities in Hilbert spaces. The proposed algorithm is a variant of the operator extrapolation method regularized using the Halpern scheme. The algorithm has an advantage over the Korpelevich extragradient method and the method of extrapolation from the past in terms of the amount of calculations required for the iterative step. For variational inequalities with monotone, Lipschitz continuous operators acting in Hilbert space, a theorem on strong convergence of the method is proved.

Робота присвячена дослiдженню нового iтерацiйного алгоритму для розв’язання варiацiйних нерiвностей в гiльбертових просторах. Запропонований алгоритм є регуляризованим за допомогою схеми Гальперна варiантом методу операторної екстраполяцiї. За об’ємом необхiдних для здiйснення iтерацiйного кроку обчислень алгоритм має перевагу над екстаградiєнтним методом Корпелевич та методом екстраполяцiї з минулого. Для варiацiйних нерiвностей з монотонними, лiпшицевими операторами, що дiють в гiльбертовому просторi, доведено теорему про сильну збiжнiсть методу.
Регуляризований алгоритм операторної екстраполяцiї
Keywords: variational inequality; monotone operator; operator extrapolation algorithm; Halpern method; варiацiйна нерiвнiсть; монотонний оператор; алгоритм операторної екстраполяцiї; метод Гальперна